2019
DOI: 10.1016/j.jss.2018.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding and Thromboembolism After Traumatic Brain Injury in the Elderly: A Real Conundrum

Abstract: Background: Elderly patients presenting with a traumatic brain injury (TBI) often have comorbidities that increase risk of thromboembolic (TE) disease and recurrent TBI. A significant number are on anticoagulant therapy at the time of injury and studies suggest that continuing anticoagulation can prevent TE events. Understanding bleeding, recurrent TBI, and TE risk after TBI can help to guide therapy. Our objectives were to 1) evaluate the incidence of bleeding, recurrent TBI, and TE events after an initial TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…There is controversy regarding the exact nature of hemostatic disruption after TBI, and evidence exists to support the presence of both a hyper-and hypocoagulable state [2]. While the initial head injury often leads to impaired clot formation and exacerbation of hemorrhagic lesions [2,[7][8][9], TBI is also independently associated with an increased risk of venous thromboembolism [10][11][12][13] and ischemic stroke [14][15][16][17][18]. Most likely, there is a progression from early increased bleeding risk to a later prothrombotic state.…”
Section: Introductionmentioning
confidence: 99%
“…There is controversy regarding the exact nature of hemostatic disruption after TBI, and evidence exists to support the presence of both a hyper-and hypocoagulable state [2]. While the initial head injury often leads to impaired clot formation and exacerbation of hemorrhagic lesions [2,[7][8][9], TBI is also independently associated with an increased risk of venous thromboembolism [10][11][12][13] and ischemic stroke [14][15][16][17][18]. Most likely, there is a progression from early increased bleeding risk to a later prothrombotic state.…”
Section: Introductionmentioning
confidence: 99%
“…30 In recent studies, it was demonstrated that in hospitalized older patients with traumatic brain injury (TBI) and in patients with greater TBI severity, incidence of acute thromboembolic events was significantly higher. 31,32 It is possible that patients with TBI and intracranial hemorrhage may have prophylaxis withheld, thereby exposing these patients to an increased risk for thromboembolic disease. However, it is noted in our study that 120 patients sustained a head injury and only seven (5.8%) had a thromboembolic event which is a similar rate to the overall thromboembolic event rate of 6.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial bleeding, edema and coagulopathy are major predictors of mortality and morbidity of TBI that still lacks of effective therapy [9,53,54]. YB and its major active ingredient Notoginseng saponins (PNS) have dual anti-hemorrhage and anti-hemostasis properties [19,55].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical removal of intracranial hematoma and fractured brain tissue (craniotomy/decompression craniectomy) can reduce the mortality of severe TBI, incidence of ICP, and length of hospital stay in TBI patients [2][3][4]. Surgery, however, could also worsen the clinical outcomes of TBI [5,6], partly due to secondary injury, increased gastrointestinal bleeding and in ammatory complications [4,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%